Un surtitrage fonctionnel, artistique ou intermédial ? Réalités théâtrales multilingues à l’ère numérique - Laliberté, Michèle (Theatre Research in Canada / Recherches théâtrales au Canada, 2017)
The aim of this study by Michèle Laliberté is to describe the characteristics of interlingual surtitling for contemporary theatre performances, along with factors that may have a negative impact on quality. More specifically, it seeks to identify the needs of translators/adaptors, presenters and creators involved in the surtitling process, and to describe their experiences with surtitling software. Laliberté’s methodology consisted of carrying out a literature review in French, English and German, and then developing a questionnaire, which she then sent to 475 theatre directors and other stakeholders in Canada with an interest in this topic (e.g., festival directors, presenters and venue directors). Her analysis was further based on excerpts from video recordings of shows and interviews with professional surtitlers and creators working in France, Germany and Canada. The study reveals that no stakeholders in Canada are currently using professional surtitling software specifically designed for live performance. The analysis also shows that there are three main types of surtitling—functional, artistic and intermedial— and that creators’ and presenters’ needs are often quite diﬀerent. Laliberté points out that although functional surtitling is used in most theatres and live performance venues, creators are increasingly opting for artistic surtitling, which can also include intermedial components. Theatre performance, writes Laliberté, is part of a fast-changing world in which multimedia is becoming more and more prominent. The translators and adaptors of the future will increasingly be required to wear several hats and to integrate not only surtitles onto the stage, but also images, videos and other visual elements.